(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Communication is essential for promoting international cooperation and economic growth in a world that is becoming more interconnected by the day. The demand for English has been increasing for many years. In addition to situations related to study, it also plays an important role in diplomatic trade. This article examines the importance and development of English for Specific Purposes (ESP), a focused area of English adapted to professional and academic needs, in two key global sectors: trade and diplomacy. It shows how important it is for people working in global business and diplomay to have special English skills, such as knowing job- specific words, using formal language, and understanding different cultures.